2011
DOI: 10.1016/j.rehab.2011.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Oral anticoagulant treatment – Evaluating the knowledge of patients admitted in physical medicine and rehabilitation units

Abstract: These results suggest that specific drug therapy management sessions should be developed as part of PM&R's therapeutic education programs for patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
9

Year Published

2011
2011
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
5
0
9
Order By: Relevance
“…Surprisingly, the majority of patients showed knowledge gaps when asked "What to do in case of a missed dose" (item 6), while around one-quarter of patients ignored what happens in case of underdosage or overdosage. A study investigating patient knowledge about warfarin found also that only half of the patients or fewer knew what happens in case of a missed dose, overdosage, or underdosage [30].…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, the majority of patients showed knowledge gaps when asked "What to do in case of a missed dose" (item 6), while around one-quarter of patients ignored what happens in case of underdosage or overdosage. A study investigating patient knowledge about warfarin found also that only half of the patients or fewer knew what happens in case of a missed dose, overdosage, or underdosage [30].…”
Section: Discussionmentioning
confidence: 99%
“…Patient education about the risks of SM when treated with anticoagulant is crucial. Despite efforts in this area, the knowledge of patients on anticoagulant drugs is still poor 21, thus favouring the occurrence of ADRs caused by DDI.…”
Section: Discussionmentioning
confidence: 99%
“…[17,23,24] Gras-Champel ve ark. 'nın OAT alan hastaların bilgi dü-zeylerinin düşük olduğuna vurgu yaptıkları çalışmada hastaların %88'inin INR kontrollerine uydukları bildirilmiştir.…”
Section: Discussionunclassified